A new sesquiterpene lactone glycoside and a new quinic acid methyl ester from Patrinia villosa. Issue 10 (2nd October 2016) - Yang, Yong-Fen; Ma, Hong-Mei; Chen, Gang; Wang, Hai-Feng; Xiang, Zheng; Feng, Qing-Mei; Hua, Hui-Ming; Pei, Yue-Hu
Abstract: A new sesquiterpene lactone glycoside (1 ) and a new quinic acid methyl ester (2 ) were isolated from Patrinia villosa, together with another two known compounds chlorogenic acid n -butyl ester (3 ), 3, 4-di- O -caffeoylquinic acid methyl ester (4 ). Their structures were established using 1D/2D-NMR spectroscopy, mass spectrometry, and comparing with spectroscopic data reported in the literature.